Spatial learning abilities in males and females of the subterranean rodent Ctenomys talarum - Mastrangelo, Matias Enrique (2010)
Few studies have focused on sex differences in spatial learning in subterranean rodents. Ctenomys talarum inhabits complex burrow systems, with males occupying larger areas than females. We assessed spatial learning ability measuring the capacity of C. talarum individuals to solve appetitive radial or longitudinal spatial tasks during the non reproductive season. We found that, regardless of sex differences in home-range size, males and females performed similarly in both tasks, improving rapidly their spatial performance after the initial trials and maintaining an accurate performance during subsequent trials. Our results show that sex differences in home-range sizes may not always lead to the evolution of sexually dimorphic spatial abilities.